Miocardite chagásica em caninos no Estado do Rio Grande do Sul - Pavarini, Saulo Petinatti; de Oliveira, Eduardo Conceição; Bandarra, Paulo Mota; Leal, Juliano Souza; Umezawa, Eufrosina Setsu; Rozza, Daniela Bernadete [UNESP]; Driemeier, David (My University, 2009)
Acute Chagas disease caused sudden death in two dogs from Porto Alegre rural zone of, Rio Grande do Sul, southern Brazil. A 9-month-old Pit Bull male (dog 1) and a 2-year-old Labrador Retriever female (dog 2) died in January 2005 and May 2008, respectively. At necropsy, the hearts were enlarged. In dog 2, heart was remarkably globoid with multiple pale areas scattered in the myocardium, especially in the right ventricle. Heart chambers, especially in the right side, were dilated. Histological findings were similar in both cases and consisted of diffuse non suppurative myocarditis predominantly with lymphocytic interstitial infiltrates. Within myocardial fibers were observed pseudocysts filled with amastigotes forms of Trypanosoma cruzi. Serologic test TESA-blot resulted positive in samples from dog 2 and showed IgM e IgG anti-T.cruzi antibodies characteristic of acute Chagas disease. The results indicate that Trypanosoma cruzi infection must be considered in the differential diagnosis of sudden death in dogs in southern Brazil and that the specie may act as a reservoir and sentinel for the disease in human beings.
Chagasic myocarditis in dogs in Rio Grande do Sul
Keywords: Chagasic myocarditis; Dogs; Trypanosoma cruzi